Discursos interpelativos de George W. Bush (2000-2004) : nacionalismo e neoconservadorismo na busca de legitimação doméstica para a guerra ao terrorismo - Felini, Carina Rafaela de Godoi (2017)
This dissertation uses the Content Analysis methodology to analyze three official speeches given by US President George W. Bush (2000-2004) after the terrorist attack on September 11, 2001. The aim is to identify the Arguments used by the president to create a national and global counter-terrorism counterpart, called the Bush Doctrine, to introduce War on Terror, legitimizing the invasion of Afghanistan (2001) and the War on Iraq (2003). Such arguments evoke elements of American national identity that reactivated American nationalism and served to obtain domestic support for those military actions. It is also considered that the neoconservative component of American nationalism was present in these discursive interpellation efforts of President George W. Bush.